Pemikiran Politik Islam Zainal Abidin Ahmad - Fisher Zulkarnain (TSAQAFAH, 2017)
Zainal Abidin Ahmad is a prominent Muslim intellectual and political expert from Masyumi who was formed by self-made or self-taught who lived before and after the independence of Indonesia. His ability mastering Arabic, Dutch and English is the most valuable asset so that he is able to master knowledge independently. This makes him in tune with other Masyumi leaders who have formal education graduates. He was also known as the "ideologue" of the Masyumi Party and held the post of Deputy chairman of the Majelis Perwakilan Rakyat Sementara (MPRS) as well as party envoy to the constituent assembly of 1955. However, he was not well known in comparison to other Masyumi figures such as Mohammad Natsir and Sjafruddin Prawiranegara. Zainal Abidin Ahmad poured his thoughts by writing books related to Islamic politics. The number of books he wrote was no less than 30 titles. This achievement made him one of the most prominent Islamic figures to write books in his era. The books he wrote are always related to Islam, especially with regard to Islamic political thought of the ancients or ideas that have relevance in its time. This article keen interest in synthesizing Islam with the state, and also highlights his various political views as well as analyzes Ahmad's in practical politics through his works.